Preparation and characterization of cellulose and microcrystalline cellulose isolated from waste Leucaena leucocephala seeds - Husin, Maryam; Li, Abd Rashid; Ramli, Norfadhilah; Romli, Ahmad Zafir; Hakimi, Mohd Idham; Ilham, Zul (Institute of Advanced Science Extension, 2017)
Cellulose and microcrystalline cellulose (MCC) were isolated from waste Leucaena leucocephala seeds (LLS) by using acid hydrolysis method. Waste LLS are unused residues after extraction of oil for conversion to biodiesel. Cellulose from LLS (LLS-cellulose) has been isolated by using 80% acetic acid and 65% nitric acid to yield 33% cellulose. MCC was further prepared from the LLS-cellulose via the acid hydrolysis method and yield 71%. The obtained LLS-cellulose and LLS-MCC samples were comparatively investigated by Fourier transform infrared spectroscopy (FTIR), Thermogravimetric analysis (TGA), X-ray diffraction (XRD) and Field Emission Scanning Electron Microscopy technique (FESEM). FTIR second derivative showed the presence of minor amounts of bound hemicellulose and relatively free of lignin compound. The crystallinity index of LLS-cellulose is higher than LLS-MCC, indicating higher crystallize size and thermal decomposition. FESEM image also showed that there is smooth surface of raw LLS after hot boiling extraction for 2 hours. Thus, this study revealed that the lignin and hemicelluloses can be removed efficiently by using hot water treatment. In addition, cellulose components produced from waste LLS could be used as precursors of other industrial applications.